Six additional replies – one more chorus of the S3 ballad. Issue 8 (2nd August 2020) - Foray, Dominique
ABSTRACT: This paper has been written as a response to 'Six additional questions about smart specialization: implications for regional innovation policy 4.0' by M. Benner. The paper starts with the argument that recent academic work has enabled considerable progress to be made, regarding both the concept and its implementation, while, on the other hand, the actual practical implementations have not evolved very much and remain strongly marked by the original instructions given by the Commission and its experts. A logical consequence of such discrepancy between theory and actual practice is that the questions asked or criticisms expressed should always clearly specify whether they concern the theory or actual implementation of this theory. They should thus endeavour to avoid confusing the two levels. The paper shows then that this is not really the case in Benner's article.